Influencia de las técnicas de relajación y manejo del estrés en pacientes con DM2 e hipertensión arterial - Rodríguez Sevillano, Brendha Liliana (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
Diabetes Mellitus type 2 and essential hypertension are frequently accompanied with stress. The relaxation techniques help the patients to live with the stress. OBJECTIVE: Identify the changes in the lifestyle and the stress response in patients with DM type 2 as an effect of the practice of relaxation techniques. MATERIAL AND METHODS: study design quasi - experimental. 15 patients were included, they were compared with a group in which patients didn’t received relaxation techniques. The following measurements were made at the beginning and at the end of the study: glucose, urea, creatinine, cholesterol, triglycerides, and uric acid, ECG and thorax teleradiography. The survey Hamilton was applied to measure the stress and the survey IMEVID evaluated the lifestyle. The intervention consisted in 14 sessions of the program to life with the stress and the relaxation techniques. The arterial blood pressure was measured at the beginning and at the end of each session. STATISTICAL ANALYSIS: to evaluate the sample, the respective confidential indexes were calculated for both instruments (HAMILTON and IMEVID), through the cronbach alpha. The Kolmogorov Smirnov test was used to identify the fdiferences between the groups . The p < 0.05 were statistically significant. RESULTS: The intervention modified anxiety and the lifestyle improved after the realized intervention significantly of p < 0.05. A decrease was obtained in the plasmatic glucose, p < 0.05. CONCLUSIONS: The study showed: significant decrease in the grade of anxiety, and a significantly modification of the lifestyle,and the glucemic control was improved with this intervention

La diabetes mellitus e hipertensión arterial, con frecuencia se acompañan de estrés. Las técnicas de relajación ayudan a disminuir el estrés. OBJETIVO: Identificar cambios en el estilo de vida y respuesta al estrés de pacientes con DM2 e HAS, después de la practica de técnicas de relajación y manejo del estrés. MATERIAL Y METODOS: estudio Cuasi- experimental. Se incluyeron 15 pacientes comparados con un grupo de pacientes que no recibieron técnicas de relajación, se realizaron mediciones al inicio y final de la intervención: glucosa, urea, creatinina, colesterol, triglicéridos, y ácido úrico, ECG y tele tórax. Se aplico la encuesta Hamilton para medir estrés y la encuesta IMEVID para medir estilo de vida. Se realizaron 14 sesiones del programa de manejo del estrés y técnicas de relajación. La presión arterial se midió al inicio y final de cada sesión. ANALISIS ESTADISTICO: Para evaluar la muestra, se calcularon los respectivos índices de confianza para ambos instrumentos (HAMILTON e IMEVID), con el alfa de cronbach. Para elegir el método estadístico se efectuó el procedimiento de test de normalidad de Kolmogorov Smirnov. Los p valores < 0.05 fueron estadísticamente significativos. RESULTADOS: La intervención modificó el grado de ansiedad, y mejoró el estilo de vida, de estos pacientes, p <0.05. Se obtuvo una disminución en la glucosa plasmática, con una p < 0.05. CONCLUSIONES: el estudio mostró: disminución significativa en el grado de ansiedad, modificación favorable y estadísticamente significativa del estilo de vida. El control glucémico mejoró con el impacto de estas modificaciones.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4103; info:eu-repo/classification/cti/3; FCMB-E-2007-0003; Pacientes; DM2; Hipertensión arterial